2022
DOI: 10.1007/s40120-022-00362-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specificity of TPS Brain Stimulation Effects in Patients with Alzheimer’s Disease: A Follow-up fMRI Analysis

Abstract: Introduction Transcranial pulse stimulation (TPS) has been recently introduced as a novel clinical brain stimulation technique based on highly focused ultrasound pressure pulses. In a first pilot study on clinical effects of navigated and focused ultrasound neuromodulation, a dichotomy of functional effects was found: patients with Alzheimer’s disease improved cognition and language but deteriorated with visuo-constructive functions. Methods We analyzed changes in funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Except for figural capacity, the memory and verbal capacity of AD patients improved significantly after TPS treatment and remained stable for 3 months. 25 A study by Dörl et al 27 also demonstrated a trend in declining visuo-constructive capabilities (CERAD figural score) and correspondingly global efficiency when the important visuoconstructive network nodes were omitted during TPS. This decline was compatible with the natural progression of the disease.…”
Section: Cognitive Improvement In Admentioning
confidence: 97%
“…Except for figural capacity, the memory and verbal capacity of AD patients improved significantly after TPS treatment and remained stable for 3 months. 25 A study by Dörl et al 27 also demonstrated a trend in declining visuo-constructive capabilities (CERAD figural score) and correspondingly global efficiency when the important visuoconstructive network nodes were omitted during TPS. This decline was compatible with the natural progression of the disease.…”
Section: Cognitive Improvement In Admentioning
confidence: 97%
“…Using the MR technique of asymmetric spin echo labeling, Nicodemus et al [26] report a local perfusion increase after sonication with a non-focal diagnostic system. Beisteiner et al, [6] Popescu et al, [27] Matt et al [28] and Dörl et al [29] applied task-based functional magnetic resonance imaging (fMRI), resting-state fMRI and MRI cortical thickness [24] Diagnostic system (GE-LOGIQe) Inferolateral frontal lobe 31 patients with chronic pain Pain reduction in back pain patients, affect improvement…”
Section: Clinical Effects With Ultrasound Neuromodulationmentioning
confidence: 99%
“…[ 28 ] and Dörl et al. [ 29 ] applied task‐based functional magnetic resonance imaging (fMRI), resting‐state fMRI and MRI cortical thickness analyses. They report brain activation increases in task specific brain areas, connectivity increases within the diseased brain network, and reduced brain atrophy in disease specific brain areas.…”
Section: Clinical Effects With Ultrasound Neuromodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first clinical study with highly focused navigated pulses has been performed with the TPS technology [ 13 ]. In this multicenter clinical study with Alzheimer patients, TPS was shown to be safe and specifically improve cognition, memory and depression scores [ 13 , 17 , 18 ]. Later, navigated FUS studies investigated patients with disorders of consciousness [ 19 , 20 ], Alzheimer’s disease [ 21 ] and epilepsy [ 22 ].…”
Section: Introductionmentioning
confidence: 99%